Pantang Larang dalam Masyarakat Kampar dan Relevansinya dengan Pendidikan Karakter - Nurmalina Nurmalina (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2015)
Abstinence is banned or prohibited acts job to do so by the people who accompanied sanctions warmth of the ancestors. The others believe that abstinence forbids irrelevant to modern-paced life as it is today. Literature has a great potential to bring people to the direction of change in character. This research is a qualitative descriptive study. The object of research is abstinence which is prohibited by the Malay community Kampar. The results showed that abstinence forbids the Kampar Malay community can be categorized into: (1) time, namely: at night, dusk; (2) place, namely: in the fields, in the middle of the road, in the woods, and in the grave; (3) safety of life, namely: death, pain, and bad luck or unfortunate; (4) based on the cycle of life (5) and occult beliefs; (6) work and activities, namely: people give birth and nurse the baby, take care of the dead and to the cemetery, walking, playing, working, making the house, table manners. The expression of abstinence forbids have relevance on character education.